The Impact of a Philippine-US FTA: The Case of Philippine Agriculture - Liborio S. Cabanilla; U-Primo E. Rodriguez (Philippine Institute for Development Studies (PIDS), 2006)
The paper examines the effect of an RP-US FTA in the Philippine agricultural sector. Using an Applied General Equilibrium (AGE) Model, it analyzes the impact of the removal of tariffs on imports from the US on the various commodities in agriculture and food processing. The simulation results suggest that most of the commodities in these sectors experience gains in output and employment following the removal of Philippine tariffs on its imports from the U.S. It also shows that the benefits of agriculture and food processing from the FTA are larger with a comprehensive removal of tariffs.
Keywords: 330; economic/development modelling; Philippine agriculture production; consumption and employment; foreign and domestic markets; tariff change and removal; Internationale Wirtschaftsbeziehungen; Freihandelszone; Handelsliberalisierung; Agrarproduktion; Philippinen; USA; Wirkungsanalyse